Behavioral and cognitive factors in entrepreneurship: entrepreneurs as the active element in new venture creation - Baron, Robert A. (Strategic Entrepreneurship Journal, 2007)
Abstract Entrepreneurs play a central role in new venture creation. Because they do, careful attention to relevant aspects of their behavior and cognition can offer useful insights into key aspects of this complex process. Specifically, investigation of carefully selected behavioral and cognitive factors can add appreciably to our understanding of the basic processes that underlie new venture creation (e.g., how opportunity recognition or creation actually occurs, how and what entrepreneurs learn from increasing experience in launching and operating new ventures). Evidence is reviewed concerning the role of behavioral and cognitive factors in several key activities performed by entrepreneurs. In addition, the potential role of a variable that has not yet been systematically investigated in the context of new venture creation— affect —is explored. Finally, suggestions are offered for future research designed to further explicate the role of behavioral and cognitive factors in new venture creation (e.g., research on the role in entrepreneurship of self‐regulatory and metacognitive mechanisms; research on the cognitive and foundations of entrepreneurial alertness). Copyright © 2007 Strategic Management Society.